An overview of the vaccine platforms to combat COVID-19 with a focus on the subunit vaccines. (March 2023) - Bayani, Fatemeh; Hashkavaei, Negin Safaei; Arjmand, Sareh; Rezaei, Shokouh; Uskoković, Vuk; Alijanianzadeh, Mahdi; Uversky, Vladimir N.; Ranaei Siadat, Seyed Omid; Mozaffari-Jovin, Sina; Sefidbakht, Yahya
Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is an emerging virus that has caused the recent coronavirus disease (COVID-19) global pandemic. The current approved COVID-19 vaccines have shown considerable efficiency against hospitalization and death. However, the continuation of the pandemic for more than two years and the likelihood of new strain emergence despite the global rollout of vaccination highlight the immediate need for the development and improvement of vaccines. mRNA, viral vector, and inactivated virus vaccine platforms were the first members of the worldwide approved vaccine list. Subunit vaccines. which are vaccines based on synthetic peptides or recombinant proteins, have been used in lower numbers and limited countries. The unavoidable advantages of this platform, including safety and precise immune targeting, make it a promising vaccine with wider global use in the near future. This review article summarizes the current knowledge on different vaccine platforms, focusing on the subunit vaccines and their clinical trial advancements against COVID-19. Graphical abstract: Image 1